2014
DOI: 10.4172/2161-105x.1000164
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Administration of Curcumin Abates the Incidence of Hypobaric Hypoxia Induced Pulmonary Edema in Rats: A Molecular Approach

Abstract: Background and purpose: High Altitude Pulmonary Edema (HAPE) is a severe high altitude illness with serious pulmonary manifestations. The present study reports benefits of prophylactic administration of curcumin in prevention of hypoxia induced pulmonary edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Recently, evidence shows that prophylactic application of curcumin decreased the inflammation resulting in a reduced influx of fluid in lungs of rats under hypoxia. This was through downregulation of the pro‐inflammatory cytokines and cell adhesion molecules by modulation of NF‐кB activity and stabilizing hypoxia‐inducible factor 1‐alpha (HIF1‐α), leading to downregulation of angiogenic molecules such as VEGF followed by a reduction in pulmonary oedema and albumin extravasation in the bronchoalveolar lavage fluid of rats (T. Mathew & Sarada, 2015; Sagi, Mathew, & Patir, 2014; Titto, Ankit, Saumya, Gausal, & Sarada, 2020).…”
Section: The Potential Effect Of Curcumin In the Treatment Of Pulmonamentioning
confidence: 99%
“…Recently, evidence shows that prophylactic application of curcumin decreased the inflammation resulting in a reduced influx of fluid in lungs of rats under hypoxia. This was through downregulation of the pro‐inflammatory cytokines and cell adhesion molecules by modulation of NF‐кB activity and stabilizing hypoxia‐inducible factor 1‐alpha (HIF1‐α), leading to downregulation of angiogenic molecules such as VEGF followed by a reduction in pulmonary oedema and albumin extravasation in the bronchoalveolar lavage fluid of rats (T. Mathew & Sarada, 2015; Sagi, Mathew, & Patir, 2014; Titto, Ankit, Saumya, Gausal, & Sarada, 2020).…”
Section: The Potential Effect Of Curcumin In the Treatment Of Pulmonamentioning
confidence: 99%
“…CURC, Figure 1b, the dietary pigment extracted from turmeric, is considered a very promising natural drug substance, although the poor water solubility of the compound at acidic pH values and its fast hydrolysis at neutral and basic ones represents an issue to be overcome prior to formulation of any CURC-based drug [1]. A constantly increasing number of publications have shown that CURC displays notable effects, not only as an anti-inflammatory compound [2,3,4] and a potent antioxidant [5,6,7,8], but also as a chemopreventive [9,10] and chemotherapeutic [9,11,12] agent. Moreover, it seems to have potential in the treatment of Alzheimer’s disease [13] and cystic fibrosis [14], as well as being considered a model substance for the treatment of HIV-infections and an immune-stimulating agent [15].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the potential of curcumin to target critical steps of the viral replication cycle, previous studies have shown that curcumin can be effectively used to treat devastating outcomes of COVID-19 infection (Zahedipour et al 2020 ). For example, it can be used to treat COVID-19 associated pulmonary inflammation (Avasarala et al 2013 ; Ferreira et al 2015 ), pulmonary edema (Mathew et al 2015; Sagi et al 2014 ; Titto et al 2020 ) and pulmonary fibrosis (Chen et al 2008 ; Cutroneo et al 2007 ; Punithavathi et al 2000 , 2003 ; Tourkina et al 2004 ; Venkatesan et al 1995 ; Venkatesan 1999 ; Xu et al 2007 ), cardiovascular damage (Li et al 2017 ; Sahebkar and Henrotin 2016 ; Salabei and Conklin 2013 ), kidney damage (Sun et al 2017 ; Xu et al 2018 ), oxidative stress in viral infection (Dai et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%